PENGARUH SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PERUSAHAAN - Nanik Lestari; Surya Irma (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to examine the impact of disclosure of sustainability economic (EC), social dimension (SO) and environmental dimension (EN) on issuer's financial performance in 2012-2015 period in mineral and mineral mining sector, energy, gas and petroleum, and infrastructure, and companies that won the SRA (Sustainability report Award) competition in 2015, each winning 1, 2, 3. The research method used in this research is quantitative approach, using cross section data. and it have 40 sample of firm. The independent variables in this study are sustainability reports as measured by economic dimensions (EC), Social (SO), and Environment (EN). The dependent variable in this study is the company's financial performance which can be measured by liquidity ratio, solvability, activity, profitability and investment. Regression used in this research is multiple regression. The result of the research shows that there is influence of sustainability report of economic dimension (EC) with company financial performance. The sustainability report of social dimension and environmental dimension has no effect on company's financial performance. The results of this study are expected to provide benefits to companies, investors, and other stakeholders in the various functions of sustainability reporting mechanisms. The author uses only one control variable are firm size, if adding another control variable, there may be an independent variable influence on the dependent.